Variability in L2 phonemic learning originates from speech-specific capabilities: An MMN study on late bilinguals*. Issue 5 (20th July 2015) - DÍAZ, BEGOÑA; MITTERER, HOLGER; BROERSMA, MIRJAM; ESCERA, CARLES; SEBASTIÁN-GALLÉS, NÚRIA
Abstract : People differ in their ability to perceive second language (L2) sounds. In early bilinguals the variability in learning L2 phonemes stems from speech-specific capabilities (Díaz, Baus, Escera, Costa & Sebastián-Gallés, 2008 ). The present study addresses whether speech-specific capabilities similarly explain variability in late bilinguals. Event-related potentials were recorded (using a design similar to Díaz et al., 2008 ) in two groups of late Dutch–English bilinguals who were good or poor in overtly discriminating the L2 English vowels /ε-æ/. The mismatch negativity, an index of discrimination sensitivity, was similar between the groups in conditions involving pure tones (of different length, frequency, and presentation order) but was attenuated in poor L2 perceivers for native, unknown, and L2 phonemes. These results suggest that variability in L2 phonemic learning originates from speech-specific capabilities and imply a continuity of L2 phonemic learning mechanisms throughout the lifespan.